2016
DOI: 10.3389/fimmu.2016.00450
|View full text |Cite
|
Sign up to set email alerts
|

Immunosenescence-Related Transcriptomic and Immunologic Changes in Older Individuals Following Influenza Vaccination

Abstract: The goal of annual influenza vaccination is to reduce mortality and morbidity associated with this disease through the generation of protective immune responses. The objective of the current study was to examine markers of immunosenescence and identify immunosenescence-related differences in gene expression, gene regulation, cytokine secretion, and immunologic changes in an older study population receiving seasonal influenza A/H1N1 vaccination. Surprisingly, prior studies in this cohort revealed weak correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 94 publications
1
36
0
Order By: Relevance
“…These observations may be attributable to "immunosenescence," i.e. an age-related decline in immune function accompanied by the dysfunction of chemokine signaling pathways [45]. In contrast, younger subjects are more likely to survive after H7N9 infection [2,[10][11][12][13][14].…”
Section: Figure 3: Changes In Core Cytokine Levels In Virus-infected mentioning
confidence: 99%
“…These observations may be attributable to "immunosenescence," i.e. an age-related decline in immune function accompanied by the dysfunction of chemokine signaling pathways [45]. In contrast, younger subjects are more likely to survive after H7N9 infection [2,[10][11][12][13][14].…”
Section: Figure 3: Changes In Core Cytokine Levels In Virus-infected mentioning
confidence: 99%
“…In addition we must collect disaggregated gender-relevant data that defines the various dimensions of this global epidemic. Moreover, aging studies in both sexes indicate diminished innate immune responses, and further analysis utilizing co-morbidities may provide the predilection for clinical worsening seen with this infection 13,32 . Taken together, registry data capturing socio-economic and co-morbidity characteristics and clinical protocols targeting the various components of the innate immune system should be explored to address the sex-specific differences in COVID infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have shown an estimated R0 of 2.2 for COVID19, there is a broad range of values for the CFR given the inability to estimate during the early phase of this outbreak realiably. The risk for mortality shows an increase in the elderly population 13 and in those with certain pre-existing conditions related to decreased or marginal cardiac, pulmonary, renal functions, and immunosuppressive states. Another area that is gaining attention is the biological sex differences in the incidence of infection and CFR*.…”
Section: Introductionmentioning
confidence: 99%
“…Age and biologic sex were included as candidate features in all models that leveraged flow cytometry data; however, the ML model did not select age or sex in cross-validated models, likely due to their known correlations with genetic features (4, 5355). Flow levels were critical in all expression-based models, either through their direct inclusion or through the interpretation of gene expression features.…”
Section: Discussionmentioning
confidence: 99%